Quantification of postural stability in minimally disabled multiple sclerosis patients by means of dynamic posturography: an observational study. Issue 1 (December 2017) - Grassi, Lucia; Rossi, Stefano; Studer, Valeria; Vasco, Gessica; Motta, Caterina; Patanè, Fabrizio; Castelli, Enrico; Rossi, Silvia; Cappa, Paolo
Abstract Background Multiple Sclerosis (MS) is a widespread progressive neurologic disease with consequent impairments in daily activities. Disorders of balance are frequent and equilibrium tests are potentially useful to quantify disability and to verify treatment effectiveness. The fair sensitivity of the widely used not-perturbed tests to detect balance disturbances in MS patients have prompted the development of mechatronic systems capable to impose known equilibrium perturbations, in order to challenge the balance control and, consequently, to better assess the level of impairment. We sought to clarify whether the proposed perturbed-test is capable to discriminate healthy subjects from patients with MS, even in mild or in the absence of clinically evident balance disturbances. Methods We assessed balance performances of 17 adults with MS and 13 age-matched healthy controls (HC) using both perturbed (PT) and not-perturbed (NPT) postural tests by means of a 3 Degree Of Freedom (DOF) rotational mechatronic platform. Participants stood barefoot on the platform in standing position and their center of pressure (CoP) was gathered by using a pressure matrix. Each trial lasted 30 s and was carried out with and without visual stimuli. Several postural indices were computed for each trial. Correlations between postural indices and clinical scales were analyzed. Results No significant differences were found between groups for all indices when subjects performed NPTs. Conversely, significant differences in postural indices between MS and HC emerged during PTs. Additionally, PTs revealed significant differences between patients without any cerebellar impairment (cerebellar EDSS subscore equal to 0) and HC. The discrimination capability of PTs was confirmed by the ROC analysis. No significant change of the selected metrics occurred in HC when NPTs were performed with eyes closed, while indices presented a significant worsening in MS subjects. Conclusions Not-perturbed tests showed lower sensitivity than perturbed ones in the identification of equilibrium impairments in minimally disabled MS patients. However, not-perturbed tests allow to better evaluate the influence of visual flow disturbances on balance control in MS. In conclusion, our findings proved that the use of the novel tests based on a 3DOF mechatronic device represents an effective tool to investigate early balance disturbances in MS.